Social Return on Investment (SROI) of mental health related interventions—A scoping review - Kadel, Rajendra; Stielke, Anna; Ashton, Kathryn; Masters, Rebecca; Dyakova, Mariana (Frontiers in Public Health, 2022)
Background There is a growing recognition of the need to effectively assess the social value of public health interventions through a wider, comprehensive approach, capturing their social, economic and environmental benefits, outcomes and impacts. Social Return on Investment (SROI) is a methodological approach which incorporates all three aspects for evaluating interventions. Mental health problems are one of the leading causes of ill health and disability worldwide. This study aims to map existing evidence on the social value of mental health interventions that uses the SROI methodology. Methods A scoping evidence search was conducted on Medline, PubMed, Google Scholar and relevant gray literature, published in English between January 2000 and March 2021 to identify studies which capture the SROI of mental health interventions in high- and middle-income countries. Studies that reported mental health outcomes and an SROI ratio were included in this review. The quality of included studies was assessed using Krlev's 12-item quality assessment framework. Results The search identified a total of 435 records; and 42 of them with varying quality met the study inclusion criteria. Most of the included studies (93%) were non-peer reviewed publicly available reports, predominantly conducted in the United Kingdom (88%); and majority (60%) of those studies were funded by charity/non-for-profit organizations. Out of 42 included studies, 22 were targeted toward individuals experiencing mental health problems and the remainder 20 were targeted to vulnerable groups or the general population to prevent, or reduce the risk of poor mental health. Eighty-one percent of included studies were graded as high quality studies based on Krlev's 12-item quality assessment framework. The reported SROI ratios of the included studies ranged from £0.79 to £28.00 for every pound invested. Conclusion This scoping review is a first of its kind to focus on SROI of mental health interventions, finding a good number of SROI studies that show a positive return on investment of the identified interventions. This review illustrates that SROI could be a useful tool and source of evidence to help inform policy and funding decisions for investment in mental health and wellbeing, as it accounts for the wider social, economic and environmental benefits of public health interventions. More SROI research in the area of public health is needed to expand the evidence base and develop further the methodology.